Determination Of The Best Private Universities Using The Analytical Hierarcy Process Method - Pandi Barita Nauli Simangunsong; Paska Marto Hasugian (Sean Institute, 2021)
Private Universities (PTS) are an option to continue post-graduate education, especially in the city of Medan. Quality private universities are very influential in carrying out education. To make it easier to compete in the world of work. Because a good PTS has a good accreditation, because PTS accreditation is very influential in the world of work. Especially in the career path, acceptance of new workers. Determining PTS in this Medan city is not easy, because there are many PTS in this Medan city. There are too many private universities in existence, making it difficult to choose PTS manually, and the results of the selection are sometimes inaccurate and become a problem in selecting the best PTS. Decision Support System (DSS) is a system that can assist a person in making accurate and targeted decisions. The method used in the Decision Support System is to use the Analytical Hierarchy Process (AHP). This method was chosen because it is able to find the best alternative from a number of alternatives, in this case the intended alternative is the one that has the right to become the best private university based on the specified criteria.